ncert 9 ex 9.2 Q no. 4
Answers
Question ---> In figure, P is a point in the interior of a parallelogram ABCD.
Show that:
(i) ar (APB) + ar (PCD) = ar (ABCD)
(ii) ar (APD) + ar (PBC) = ar (APB) + ar (PCD)
Ans. (i) Draw a line passing through point P and parallel to AB which intersects AD at Q and BC at R respectively.
Now APB and parallelogram ABRQ are on the same base AB and between same parallels AB and QR.
ar (APB) = ar (gm ABRQ) ……….(i)
Also PCD and parallelogram DCRQ are on the same base AB and between same parallels AB and QR.
ar (PCD) = ar (gm DCRQ) ……….(ii)
Adding eq. (i) and (ii),
ar (APB) + ar (PCD)
= ar (gm ABRQ) + ar (gm DCRQ)
ar (APB) = ar (gm ABCD) ……….(iii)
(ii) Draw a line through P and parallel to AD which intersects AB at M and DC at N. Now APD and parallelogram AMND are on the same base AD and between same parallels AD and MN.
ar (APD) = ar (gm AMND) ……….(iv)
Also PBC and parallelogram MNCB are on the same base BC and between same parallels BC and MN.
ar (PBC) = ar (gm MNCB) ……….(v)
Adding eq. (i) and (ii),
ar (APD) + ar (PBC)
= ar (gm AMND) + ar (gm MNCB)
ar (APD) = ar (gm ABCD) ……….(vi)
From eq. (iii) and (vi), we get,
ar (APB) + ar (PCD) = ar (APD) + ar (PBC)
or ar (APD) + ar (PBC) = ar (APB) + ar (PCD)
Hence proved.
Answer:
(i) Draw a line passing through point P and parallel to AB which intersects AD at Q and BC at R respectively.
Now APB and parallelogram ABRQ are on the same base AB and between same parallels AB and QR.
ar (APB) = ar (gm ABRQ) ……….(i)
Also PCD and parallelogram DCRQ are on the same base AB and between same parallels AB and QR.
ar (PCD) = ar (gm DCRQ) ……….(ii)
Adding eq. (i) and (ii),
ar (APB) + ar (PCD)
= ar (gm ABRQ) + ar (gm DCRQ)
ar (APB) = ar (gm ABCD) ……….(iii)
(ii) Draw a line through P and parallel to AD which intersects AB at M and DC at N. Now APD and parallelogram AMND are on the same base AD and between same parallels AD and MN.
ar (APD) = ar (gm AMND) ……….(iv)
Also PBC and parallelogram MNCB are on the same base BC and between same parallels BC and MN.
ar (PBC) = ar (gm MNCB) ……….(v)
Adding eq. (i) and (ii),
ar (APD) + ar (PBC)
= ar (gm AMND) + ar (gm MNCB)
ar (APD) = ar (gm ABCD) ……….(vi)
From eq. (iii) and (vi), we get,
ar (APB) + ar (PCD) = ar (APD) + ar (PBC)
or ar (APD) + ar (PBC) = ar (APB) + ar (PCD)
Hence proved.